Yield and Components of Pine (Pinus merkusii) Turpentine Among Age Class Differences Tapping by Borehole Method - Agus Sukarno; Anisa Zairina; Yani Quarta; Risca Kurniasari; Sumardi Sumardi; Amin Setyo Leksono (Postgraduate School Universitas Brawijaya, 2020)
Tapping pine oleoresin using the borehole method produces clean oleoresin, so that the yield of turpentine increases. Turpentine produced by the oleoresin processing manufactory, raw materials come from several age classes of pine. This study aims to determine the yield and component of turpentine derived from tapping the oleoresin using the borehole method. The research was conducted in the Batu production forest area, East Java, Indonesia. A total of 150 pine trees for each age class IV, V and VI were sampled from each plot. Drill bit size using a 16 mm, and oleoresin drilling is done in the morning. Furthermore, the oleoresin that comes out is accommodated using a plastic bag for two days. Oleoresin pine is then distilled with temperatures of 160-180oC. The average yield of turpentine derived from pine age class IV was 19.52%, age class V was 19.93% and age class VI was 20.94%. Turpentine component was analyzed using Gas Chromatography MS to determine its content. The results of the analysis showed that the component of turpentine which had a large percentage in each age class consisted of, Î±-pinene, Î²-pinene, limonene, trans-2 carena, Î±-terpinolene, benzenemethanol and trans-pinocarveol. However, Î²-pinene was not found in the age of class VI and trans-2 carena was not found in the age of class IV